PERLINDUNGAN HUKUM TERHADAP PIHAK PEMBELI DALAM TRANSAKSI JUAL BELI HARTA GONO – GINI OLEH SALAH SALAH SATU PIHAK DALAM PERKAWINAN KAITANNYA DENGAN KEWENANGAN SUAMI ATAU ISTERI DI TINJAU MENURUT UNDANG - UNDANG NO. 1 TAHUN 1974 - Ani Noviani (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
Abstract               As we all know that Law No. 1 of 1974 on Marriage is a work of great significance for the nation of Indonesia. An outcome that does not guarantee the realization of the unity of the family and household well-being eternal is based on God.Marriage law does not explain their interpretation of such property. However, according to Hilman Hadikusuma, is an innate property is a treasure waiting spouses or innate property in the true sense, because each spouse brings wealth as stock in a marital bond that is free and independent.Referred joint property (Gono-gini), according to him, are all revenue or income of husband and wife during the marriage bond apart from the origin and property or property that follows the administration of origin treasure is treasure living with a husband and wife.